Reconstruction of Juvenile Criminal Law in The Framework of Jinayah Fiqh - Efendi, Sumardi; Mayasari, Mayasari (STAINI Press, 2026)
Juvenile criminal law in Indonesia has undergone significant development through the application of child protection principles and restorative justice as regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law). Nevertheless, in practice, various structural and cultural problems remain that hinder the achievement of the objectives of guidance and rehabilitation for children in conflict with the law. This study aims to analyze and reconstruct juvenile criminal law in Indonesia by integrating the values of fiqh jinayah as a normative approach. This research employs a normative juridical method with conceptual and comparative approaches, through an examination of the provisions of the SPPA Law and the principles of criminal responsibility for children in fiqh jinayah. Data were obtained from primary, secondary, and tertiary legal materials, which were analyzed qualitatively and prescriptively.The results show that, normatively, juvenile criminal law in Indonesia has accommodated the principles of child protection and restorative justice; however, its implementation remains suboptimal due to institutional limitations, the limited understanding of law enforcement officers, and socio-cultural factors. On the other hand, fiqh jinayah offers relevant conceptual frameworks, particularly through the determination of the age of tamyiz (discernment) and baligh (legal maturity) as the basis for juvenile criminal responsibility, as well as the application of ta’zir sanctions that are flexible, proportional, and education-oriented.This study recommends a normative-integrative reconstruction of juvenile criminal law by combining positive law and the values of fiqh jinayah. The novelty of this research lies in formulating a model for reforming juvenile criminal law that places educational and humanistic approaches as the primary foundation of the juvenile criminal justice system in Indonesia.